Evaluation of The Implementation of Electronic Medical Records On The Completeness Of Emergency Room (IGD) Patient Documentation at Lembang Regional Hospital - Dinny Sulistiani; Intan Pujilestari (CV. Inara, 2026)
The implementation of Electronic Medical Records (EMR) is part of the digital transformation of healthcare services aimed at improving the quality of documentation and continuity of patient care. This study aims to evaluate the implementation of Electronic Medical Records on the completeness of patient documentation in the Emergency Department (IGD) at Lembang Regional General Hospital. The study used a quantitative approach with a descriptive design and an evaluative approach. The study population was 1,850 Electronic Medical Record documents from ER patients, with a sample of 329 documents determined using the Slovin formula and Simple Random Sampling techniques. Data were collected through observation, documentation studies, and quantitative analysis checklists, then analyzed using descriptive statistics in the form of frequency distribution and percentages. The results showed that the entire ER service documentation process had used Electronic Medical Records. The level of completeness of documentation reached 85.1%, while 14.9% of documents were still incomplete. The most frequently incomplete component was the doctor's signature (10.3%), followed by patient education (6.1%) and physical examination (4.6%). The conclusion of the study shows that the implementation of Electronic Medical Records at Lembang Regional Hospital has supported the completeness of IGD patient documentation, but there is still a need to improve user compliance, monitoring, and evaluation to optimize the quality of medical record documentation